Review of Chinese species of the leafhopper genus Amrasca Ghauri (Hemiptera, Cicadellidae, Typhlocybinae), with description of a new species, species checklist and notes on the identity of the Indian cotton leafhopper - Xu, Ye; Wang, Yuru; Dietrich, Christopher H.; Fletcher, Murray J.; Qin, Daozheng (Zootaxa, 2017)
The leafhopper genus Amrasca Ghauri from China is reviewed. Six species are included, of which three are reported for the first time from China. A new species, A. (Amrasca) complana Qin, Wang & Xu, sp. nov. is described based on specimens from south China. A complete checklist of the genus and an identification key to species in the Chinese fauna are provided. Jacobiasca curvata (Ahmed & Samad) comb. nov. is removed from Amrasca and A. (A.) singularis Einyu & Ahmed is treated as a species incertae sedis. Habitus photos of all Chinese Amrasca species and illustrations of male genitalia of the new species are also given. The male holotype specimen of Chlorita bimaculata Matsumura is here designated as the neotype of Empoasca biguttula Ishida to fix the identity of this economically important species and Sundapteryx Dworakowska is reinstated from synonymy as a subgenus of Amrasca. Thus, the correct scientific name of the Indian cotton leafhopper is Amrasca (Sundapteryx) biguttula (Ishida).